Smartphone Addiction Affecting Study Habit of Chittagong University Students (Chittagong University Journal of Biological Sciences, 2024)
The aim of the research was to determine the effects of smartphone addiction on study habits of university students. Data were collected from 200 students (100 males and 100 females) selected purposively from Chittagong University, Bangladesh. To collect data, Personal Information Form (PIF), Smartphone Addiction Scale–Short Version (SAS-SV) translated by Hossain and Kawser1 and Study Habit Questionnaire adapted by Ahmed, Hossain, and Rashid2 were administered on 200 undergraduates of Chittagong University. To analyze the data, t-test and regression analyses was used. Results revealed that higher smartphone usages led to lower study habits. There were statistically significant gender differences in smartphone addiction and study habits of students. In addition, statistically significant differences between residential and non-residential students were observed in case of smartphone addiction, but no significant differences were evident for study habits. A multiple regression analysis confirmed that smartphone addiction was a significant predictor that could explain 6.3% variations in study habits of university students.Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 1-7, 2024